Heat - extruded sorghum grain for growirig - finishing swine. - Cowman, G.L.; Deyoe, C.W.; Koch, B.A.; Pfost, H.B.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This paper is a progress report of a research project initiated this past year designed to study the effects of heat and pressure processing of sorghum grain on the performance of swine. The theoretical reasoning behind this approach was to increase the utilization of sorghum grain by chemical and/or physical starch damage with the application of certain degrees of heat and pressure during processing. The starch granules, which contain complex forms of chemically stored" energy, must be broken-up and reduced into simple units of glucose in the digestive tract of the pig before absorption can occur.
Swine Industry Day 1968 is known as Swine Day, 1968
Keywords: Swine; Growing-finishing swine; Heat - extruded sorghum grain